Assessing Campus Alcohol Policies: Measuring Accessibility, Clarity, and Effectiveness. (8th April 2019) - Jernigan, David H.; Shields, Kelsey; Mitchell, Molly; Arria, Amelia M.
Abstract : Background: Excessive alcohol consumption poses significant hazards to health and safety on college campuses. While substantial research exists regarding effective policies for preventing alcohol‐related problems in the communities surrounding campuses, on‐campus alcohol policies have received far less attention. Methods: Official campus alcohol policies (CAPs) were retrieved from the websites of the 15 member schools of the Maryland Collaborative to Reduce College Drinking and Related Problems, a voluntary statewide collaborative. CAPs were assessed for accessibility, clarity, and effectiveness. In addition to assessing whether campuses were in compliance with federal regulations for comprehensiveness of policies, a measure of likely policy effectiveness was developed through the use of 2 Delphi panels drawing on alcohol policy researchers and on‐campus and community practitioners, respectively. The panels rated 35 potential policies and 13 possible sanctions; lists of policies and sanctions were compiled primarily from what was already in existence at 1 or more member schools. Results: For most campuses, the CAPs could be located within 30 seconds, but tended to be spread across multiple web pages. Language used to communicate the policies tended to be complex and above the reading level of someone with a high school education. At least half of the schools had less than half of the possible policies rated most or somewhat effective by the Delphi panels. Schools were more likely to employ the most effective sanctions, but somewhat and ineffective sanctions were also not uncommon. Conclusions: CAPs are an important element in reducing negative consequences of alcohol consumption on college campuses. A higher level of research scrutiny is warranted to understand the extent to which CAPs are associated with excessive drinking, but this research describes an evidence‐ and expert‐informed assessment approach that colleges can use to regularly analyze and update their CAPS. Abstract : We piloted assessment of campus alcohol policies across four domains: clarity, accessibility, policy effectiveness, and sanctions effectiveness. Delphi panels of alcohol policy researchers and campus and community practitioners rated policies and sanctions for the anticipated levels of effectiveness. Applying these measures to the policies of 15 college and university campuses revealed specific areas where schools could strengthen their approach to excessive drinking on college campuses, and work is ongoing with the campuses to revise and improve their policies.